PENGARUH CITRA MEREK DAN KUALITAS PELAYANAN TERHADAP KEPUTUSAN PEMBELIAN ALFAMART TIBAN GAJA MADA - Hidayat, Sharif; Purba, Daris (SCIENTIA JOURNAL, 2021)
This study aims to determine the effect of (X1) brand image and (X2 service quality on (Y) purchasing decisions at Alfamart Tiban Gaja Mada by using this Random Sampling technique 354. The method of collecting data using a questionnaire that (X1) brand image and (X2 ) service quality has a positive effect on (Y) purchasing decisions based on regression results and with an R Square value. Based on statistical data, the indicators in this study are valid and reliable variables. Hypothesis testing using t test shows that (X1) brand image and ( X2) service quality proved to have a significant effect on (Y) purchasing decisions. Then through the F test it can be seen that the variable (X1) brand image and (X2) service quality simultaneously affect the purchasing decision variables with F count greater than F table